Elevated KRAS protein level is associated with better survival in pancreatic cancer - S. M. Stålberg; L. Silwal-Pandit; J. Hamfjord; D. J. H. Nebdal; J. Lehtiö; O. C. Lingjærde; B. S. Skålhegg; E. H. Kure (BMC Cancer)
Abstract Background Activating somatic KRAS mutations in hotspot loci occur almost universally (> 95%) in pancreatic ductal adenocarcinoma (PDAC). Both the presence of a KRAS mutation and high mRNA expression levels of KRAS in tumor tissue have been associated with worse outcome. Less is known about the expression of KRAS at the protein level and its association with clinical and molecular parameters. In the present study, we investigated the prognostic significance of the KRAS protein level and its relation to KRAS mutation status and the mRNA expression level. Methods A total of 41 PDAC tumors were screened for seven KRAS mutations (p.G12D, p.G12V, p.G12R, p.G12C, p.G12S, p.G13D, p.G12A) by the Wobble-enhanced ARMS method. Whole transcriptome and proteome profiles were obtained using mRNA microarrays (Agilent) and quantitative mass spectrometry-based proteomics (HiRIEF LC–MS/MS), respectively. The clinical outcome was overall survival (OS). Results KRAS mutations were identified in 88% of the tumors with p.G12D and p.G12V mutations being the most frequent. Tumors with p.G12V mutation had significantly higher KRAS mRNA expression than tumors with p.G12D, p.G12C, p.G12R or no mutation identified (P < 0.01). KRAS protein levels did not associate significantly to neither KRAS mRNA levels (Spearman’s rho = 0.18, P = 0.28) nor type of KRAS mutation. High KRAS protein level and mutation p.G12V were found to be significantly associated with better (P < 0.01) and worse OS (P < 0.05), respectively. Conclusions The KRAS protein level correlated poorly with KRAS mRNA expression level and was not significantly associated with the type of mutation present. Interestingly, we found that patients with high KRAS protein level in their tumors had a better clinical outcome.